Prediction of the Effective Thermal Conductivity of Fiber Reinforced Composites Using a Micromechanical Approach. (April 2019) - Sayyidmousavi, A.; Bougherara, H.; Falahatgar, S. R.; Fawaz, Z.
ABSTRACT: A novel micromechanical approach is proposed to calculate the effective thermal conductivities of fiber reinforced composite materials. The key advantage of the present formulation is its ability to yield closed form solutions for the effective thermal conductivity of composites in both longitudinal and transverse directions for three dimensional heat transfer problems. The obtained results are in good agreement with the experimental data reported in the literature. When compared with analytical and finite element solutions, the results are seen to be in better agreement with the hexagonal packed array compared to the square packed array which thus represents a more realistic model of the fiber distribution in the matrix medium.